Counseling on Vulva Hygiene (Genetic Hygiene) to Young Women in Neighborhood III, Baru Ladang Bambu Village, Medan Tuntungan District, 2018 - Desi Anggraini; Helena Fransysca (Institute of Computer Science (IOCS), 2019)
The purpose of this study was to determine the effect of health education by providing counseling materials on vulvar hygiene (genital hygiene) to prevent the occurrence of vaginal discharge in adolescent girls on the knowledge of female students / adolescent girls in the Ladang Bambu Village, Medan Tuntungan District. And the activities carried out to increase students' knowledge about maintaining genital hygiene (vulva hygiene) in the Ladang Bambu Village, Medan Tuntungan Subdistrict. Increase the influence of health education knowledge by teaching young women how to clean the genitalia properly, teaching young women to change underwear at least 2 times. in the Ladang Bambu Village, Medan Tuntungan District. The type and form of activity of this activity is the provision of material to students / adolescent girls about the importance of maintaining genital hygiene (vulva hygiene) to prevent vaginal discharge in young women. teach young women how to clean the genitalia, encourage teens to change their underwear at least 2 times a day or when they feel wet/humid. Results To achieve the objectives of the above activities, activities were carried out, including providing counseling materials on vulvar hygiene (genital hygiene) to prevent vaginal discharge in adolescent girls in Environment III, Ladang Bambu Village, Medan Tuntungan District. encourage teens to change underwear at least 2 times a day or when they feel wet/humid. Results To achieve the objectives of the above activities, activities were carried out, including providing counseling materials on vulvar hygiene (genital hygiene) to prevent vaginal discharge in adolescent girls in Environment III, Ladang Bambu Village, Medan Tuntungan District. encourage teens to change underwear at least 2 times a day or when they feel wet/humid. Results To achieve the objectives of the above activities, activities were carried out, including providing counseling materials on vulvar hygiene (genital hygiene) to prevent vaginal discharge in adolescent girls in Environment III, Ladang Bambu Village, Medan Tuntungan District.